Delirium in ICU patients following cardiac surgery: An observational study. Issue 9 (25th April 2018) - Simeone, Silvio; Pucciarelli, Gianluca; Perrone, Marco; Teresa, Rea; Gargiulo, Gianpaolo; Guillari, Assunta; Castellano, Gaetano; Tommaso, Luigi Di; Niola, Massimo; Iannelli, Gabriele
Abstract : Aims and objectives: To observe the clinical and structural factors that can be associated with the post‐operative onset of delirium in patients who have undergone heart surgery. Background: Several risk factors could contribute to the development of delirium, such as the use of some sedative drugs and a patient's history with certain types of acute chronic disease. However, in the literature, there is little knowledge about the association between delirium in patients who have undergone cardiac surgical intervention and their clinical and environmental predictors. Design: We used an observational design. Methods: We enrolled 89 hospitalised patients in the ICU. Patients were first evaluated using the Richmond Agitation Sedation Scale and subsequently using the Confusion Assessment Method for the ICU. A linear model of regression was used to identify the predictors of delirium in patients. Results: The patients had an average age of 89 years ( SD = 6.9), were predominantly male (84.3%) and were mostly married (79.8%). The majority of patients had been subjected to bypass (80.9%), while 19.1% had undergone the intervention of endoprosthesis. The logistic regression model showed that patient age, the duration of mechanically assisted ventilation, continuous exposure to artificial light and the presence of sleep disorders were predictors of the onset of delirium. Conclusion: This study further confirms that clinical aspects such as insomnia and one's circadian rhythm as well as structural elements such as exposure to artificial light are variables that should be monitored in order to prevent and treat the onset of severe post‐operative delirium. Relevance to clinical practice: Identifying the possible factors that predispose a patient to the onset of delirium during intensive therapy following cardiac surgery, it is fundamental to implement interventions to prevent this syndrome.